Fetal Macrosomia with Suboptimal Antenatal Care: A Case Report - Alfun Dhiya An; Indrahany Alwiandono; Asri Nur Maulidya; Restu Maharany Arumningtyas (CV. Inara, 2026)
Background: Fetal macrosomia is associated with increased maternal and neonatal morbidity. Early detection relies on adequate Antenatal Care (ANC), including appropriate metabolic screening and serial fetal growth assessment. Suboptimal ANC may delay the recognition of maternal risk factors and fetal overgrowth, particularly in high-risk pregnancies. Case presentation: We reported a case of a 46-year-old Indonesian multiparous woman with obesity who was referred from the Community Health Centre (CHC) to a secondary hospital due to post-term pregnancy, suspected fetal macrosomia, and advanced maternal age. Despite multiple ANC visits, random blood glucose testing was not documented during Integrated Antenatal Care at the CHC, the primary healthcare level. Progressive excessive maternal weight gain and marked increases in fundal height were observed during the second and third trimesters without further metabolic evaluation. An elective caesarean section was performed at 40+4 weeks of gestation, delivering a male neonate weighing 5,295 g. Post-operative evaluation revealed maternal prediabetic status, while the neonate required monitoring due to macrosomia but remained clinically stable. Conclusion: This case highlights the consequences of suboptimal antenatal screening and surveillance in high-risk pregnancies. Failure to perform a timely metabolic assessment and respond to clinical indicators of excessive fetal growth may contribute to the delayed diagnosis of fetal macrosomia. Strengthening the quality and completeness of integrated antenatal care, particularly at the primary healthcare level, is essential to improve early detection and prevent adverse maternal dan neonatal outcomes.